Simulation of Temperature Distribution in TIG Spot Welds of (Al-Mg) Alloy Using Finite Element Method - Abbas, Muna K; Al-Maliky, Abdul Hussain G.; Alkhafajy, Ahlam Abid Ameer (Al-Khwarizmi Engineering Journal, 2018)
This research concern to analyse and simulate the temperature distribution in the spot welding joints using tungsten arc welding shielded with inert gas (TIG Spot) for the aluminum-magnesium alloy type  (5052-O).      The effect of and the quantity of the heat input that enter the weld zone has been investigated welding current, welding time and arc length on temperature distribution. The finite element method (by utilizing programme ANSYS 5.4) is presented  the temperature distribution in a circular weld pool and the weld pool penetration (depth of welding) through the top sheet ,across the interface into the lower sheet forming a weld spot.                                                                                                           A three dimensional (3-D) model has been constructed to study the temperature distribution and the depth or penetration of the weld spot. The results showed that the weld zone and heat affected zone (HAZ) suffer from high temperature variation caused by severe thermal cycle. The temperature reaches the highest value of the melt metal at the weld spot 698°C at weld current 130 Amp, weld time 6 sec and arc length 1.6 mm, then drops further away from the weld spot in the direction  the base metal.      Figuers were plotted to explain the results and to show the temperature distribution and its value in the weld spot  and heat effected zone.